2005
DOI: 10.1016/j.apcatb.2004.09.021
|View full text |Cite
|
Sign up to set email alerts
|

NH3 and urea in the selective catalytic reduction of NOx over oxide-supported copper catalysts

Abstract: Abstract.The temperature programmed activity of a series of oxide supported (TiO 2 , Al 2 O 3 and SiO 2 ) Cu catalysts formed from two different Cu precursors (Cu(NO 3 ) 2 and CuSO 4 ) for the selective catalytic reduction of NO x using solutions of urea as a reductant have been determined. These activities are compared to those found using NH 3 as a reducing agent over the same catalysts in the presence of H 2 O and it is found that catalysts that are active for the selective reduction of NO x with NH 3 are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…For instance, Sullivan et al [11] introduced water and solutions of urea from a calibrated syringe driver, which is technically rather far from the industrial conditions and not adapted to vaporization of low flow. Regarding Koebel et al [9], they used a modified prototype from Bosch as dosing unit for urea injection to achieve various model-based algorithms for urea dosage in the diesel engine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Sullivan et al [11] introduced water and solutions of urea from a calibrated syringe driver, which is technically rather far from the industrial conditions and not adapted to vaporization of low flow. Regarding Koebel et al [9], they used a modified prototype from Bosch as dosing unit for urea injection to achieve various model-based algorithms for urea dosage in the diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, SCR is a continuous process. It is described as an attractive way to reduce NOx in excess of O2, with the possible use of a large choice of reductants like hydrocarbons (HC) [3][4][5][6][7][8], ammonia [9][10][11][12], urea [13], hydrogen, alcohol [14,15], etc. While HC-SCR has been largely studied in the past decades for automotive applications, the NH3-SCR is now accepted as exhibiting the highest potential to reduce NOx emission in the lean condition, with different reaction pathways described by Equations (1)- (3).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have shown that it has ideal performance in NO X conversion efficiency compared with that of urea-SCR. Sullivan and Doherty (2005) showed that NO X conversion with the H 2 O-urea-SCR is lower than that of the H 2 O-NH 3 -SCR using Cu-Al 2 O 3 and Cu-TiO 2 SCR catalysts. Koebel and Strutz (2003) presented that the NO X conversion of the NH 3 -SCR is better than that of the urea-SCR.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3] Thus, methane reforming with CO 2 to synthesis gas has gained considerable attention in the field of catalysis. [4][5][6] Noble metals (Pt, Rh, Ru, Pd) exhibit a good level of activity and selectivity in methane reforming reactions with CO 2 , [7][8][9] however, their restricted availability and high cost make them unsuitable for industrial-scale operation. In recent years, supported nickel-based catalysts have attracted increasing interest owing to their similar activity to noble-metal catalysts and low costs.…”
Section: Introductionmentioning
confidence: 99%